Role of Capped Oleyl Amine in the Moisture‐Induced Structural Transformation of CsPbBr3 Perovskite Nanocrystals. Issue 11 (28th August 2019) - Sandeep, K.; Gopika, K. Y.; Revathi, M. R.
Abstract : The moisture‐induced structural decomposition of lead halide perovskites is the major challenge in solar cells and light‐emitting diodes based on perovskites as the active material. The presence of moisture results in the structural conversion of cubic 3D CsPbBr3 nanocrystals to 2D CsPb2 Br5 nanosheets before its decomposition to PbBr2 . The capping agent used, oleyl amine, plays a crucial role in this structural transformation. The presence of moisture converts the capping agent, oleyl amine, to its salt, which transforms the 3D CsPbBr3 perovskite nanocrystals to 2D CsPb2 Br5 nanosheets. Further, these CsPb2 Br5 nanosheets decompose to trigonal PbBr2, in the presence of higher amounts of water. Also, the amount of capping agent, oleyl amine, plays an important role in the rate of moisture‐induced structural transformations. The rate of decomposition increases with the amount of oleyl amine used as a result of the reaction of water with the excess ligands. By revealing the exact mechanism of the structural alterations in the presence of water, new design strategies can be used to prevent the decomposition of perovskites. Abstract : Oleyl amine, the capping ligand of CsPbBr3 perovskites, plays a crucial role in moisture‐induced structural transformation. In the presence of moisture, oleyl amine converts to its ammonium salt, which transforms CsPbBr3 nanocrystals to CsPb2 Br5 nanosheets. Further, these nanosheets decompose into PbBr2 under prolonged water treatment. By knowing the mechanism of structural transformations, new methodologies can be adopted to prevent the moisture‐induced decomposition of CsPbBr3 perovskites.